Men Behind Bars - Wooden, Wayne S. author. aut Link
X, 264 p.
Keywords: "Barry" is a seventeen-year-old single white male. He has blond hair and blue eyes, weighs 150 pounds, and is five feet eleven inches tall. He was arrested in California at age sixteen for assault and robbery. Because he was underage he was initially segregated in a one-man cell while in county jail. Then, upon admission to a state prison recep tion and classification facility, he was housed in a special dormitory for young, inexperienced inmates who would be at risk within the general population. Upon completion of his screening Barry's counselor recommended that he be sent to a penal institution reserved for the younger, more violence-prone, and hard core inmates. Barry said that he felt he would have "prob lems" at the recommended facility, but his counselor replied, "You won't have any problems." Once he arrived, Barry was double-celled with a nineteen-year-old inmate who beat and anally raped him during his first night in the admission unit. Barry's cellmate continued to assault him sexually during the two weeks they were housed together.